2009
DOI: 10.1002/mus.21382
|View full text |Cite
|
Sign up to set email alerts
|

Elicitability of muscle cramps in different leg and foot muscles

Abstract: To explore the efficacy of muscle motor point stimulation in eliciting muscle cramps, 11 subjects underwent eight sessions of electrical stimulation of the following muscles bilaterally: abductor hallucis flexor hallucis brevis, and both heads of the gastrocnemius muscles. Bursts of 150 square wave stimuli (duration: 152 micros; current intensity: 30% supramaximal) were applied. The stimulation frequency was increased from 4 pulses per second (pps) at increments of 2 pps until a cramp was induced. The number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 23 publications
1
25
0
1
Order By: Relevance
“…Consistently, the above‐threshold stimulation allows the elicitation of involuntary contractions that present intensity and duration comparable to those of voluntarily‐ or spontaneously‐induced cramps. Moreover, in the case of electrically elicited cramps of foot and leg muscles (Minetto & Botter, 2009), the pain associated with the contraction and the delayed onset muscle soreness following the resolution of the cramp are also comparable to those in naturally occurring cramps. Another limitation of the study is that the investigator who determined the cramp threshold was not blinded to the subject's condition (intact vs .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Consistently, the above‐threshold stimulation allows the elicitation of involuntary contractions that present intensity and duration comparable to those of voluntarily‐ or spontaneously‐induced cramps. Moreover, in the case of electrically elicited cramps of foot and leg muscles (Minetto & Botter, 2009), the pain associated with the contraction and the delayed onset muscle soreness following the resolution of the cramp are also comparable to those in naturally occurring cramps. Another limitation of the study is that the investigator who determined the cramp threshold was not blinded to the subject's condition (intact vs .…”
Section: Discussionmentioning
confidence: 96%
“…Cramps were elicited in the abductor hallucis muscle of the dominant foot with electrical stimulation of the muscle motor point, as described previously (Minetto et al . 2008; Minetto & Botter, 2009). The subject was seated comfortably on a chair with the ankle in a neutral position and the foot resting on a padded support.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, electrical stimulation is often applied directly to the muscle motor point. This produces less pain, and has been developed as an alternative to peripheral nerve stimulation and has been utilized (Minetto and Botter 2009;Minetto et al 2008Minetto et al , 2009aMinetto et al , b, 2011. A study with the motor point stimulation demonstrated that the threshold frequency and pain in intrinsic foot muscle were lower than those in leg muscle.…”
Section: How To Induce Muscle Cramps?mentioning
confidence: 98%
“…A study with the motor point stimulation demonstrated that the threshold frequency and pain in intrinsic foot muscle were lower than those in leg muscle. The authors concluded that the intrinsic foot muscle is the most suitable for the study of muscle cramps (Minetto and Botter 2009). It has been found that the high frequency magnetic stimulation to peripheral nerve can provoke muscle cramps, which are less painful than those produced by electrical stimulation (Caress et al 2000).…”
Section: How To Induce Muscle Cramps?mentioning
confidence: 99%
“…Studies aimed at answering this question have used several methods to illicit cramps, such as direct electrical stimulation of nerves, which has demonstrated a lower threshold of intensity necessary to trigger cramps in cramp -prone individuals compared with those with no history of cramps. [70][71][72][73] This suggests that there may be a physiological predisposition to cramps. Fasciculations, a classic "lower motor neuron" sign, may be seen during a cramp discharge, supporting a peripheral origin of cramps.…”
mentioning
confidence: 99%